INHERITANCE OF RESISTANCE TO YELLOW MOSAIC VIRUS IN BLACK GRAM (Vigna mungo (L.) Hepper) - S. VANISRI; BHARATI N. BHAT, E. RAMBABU, CH. ANURADHA, MD. ABDUS SUBHAN SALMAN, V. SRIDHAR (The Journal of Research, PJTSAU, 2023)
Blackgram (Vigna mungo (L.) Hepper) also known as uradbean, is one of the important pulse crops of India. India is the largest producer and also consumer of blackgram. It has surely marked itself as the most popular pulse and can be most consequently referred to as the “king of the pulses” due to its delicious taste and numerous other nutritional qualities.Blackgram is superb combination of all nutrients, which contains proteins (25-26 %), carbohydrates (60 %), fat (1.5 %), minerals, amino acids and vitamins. Being a good leguminous crop, it is itself a mini-fertilizer depository, as it has special characteristics of maintaining and restoring soil fertility through fixing atmospheric nitrogen in symbiotic association with Rhizobium bacteria, present in the root nodules. It is short duration pulse crop (Delic et al. 2009), usually flowering within 30-60 days of sowing and maturing within 60-90 days.